Quasi‐1D Antiferroelectricity in Centrosymmetric CsTaS3 Crystal. Issue 6 (6th April 2022) - Bie, Jie; Zhou, Jian; Fa, Wei
Abstract: 1D ferroelectric (FE) materials are expected to be promising low‐dimensional materials for nanometer devices, but are rarely reported. The previous experiment discovered that quasi‐1D CsTaS3 crystalizes in centrosymmetric space group, but in which the Ta cations have a strange shift along the c axis from the center of TaS6 octahedron. Here, the crystal structure, electronic structure, ferroelectric, and piezoelectric properties of CsTaS3 by using first‐principles calculations are studied. It is found that the empty d orbitals of Ta cations induce the distortions of TaS6 octahedra, which bring the polarity along a given [TaS3 ] − chain. The adjacent chains are antiferroelectric (AFE) coupling making CsTaS3 being an AFE material. However, the FE phase of CsTaS3 is supposed to be accessible since its total energy is only 0.3 meV per formula higher than that of the AFE phase. The polarization of FE CsTaS3 is estimated to be 16.8 μC cm −2, which is comparable to those of well‐known FE perovskites. The work predicts a quasi‐1D AFE material, which would be helpful for subsequent experimental work. Abstract : Quasi‐1D CsTaS3 is found to be an antiferroelectric material with very weak interchain couplings and moderate intrachain polarity. The low energy barrier and moderate spontaneous polarization enable the CsTaS3 as a candidate material for field‐effect transistors with a high‐density ferroelectric switching operator.